A Comparison of Islamic Capital Market Supervision in Indonesia and Malaysia - Febbyanti Agustina Eka Putri; Wahyu Akbar; Haidi Hajar Widagdo (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research provides a comparative analysis, namely a comparison of Islamic capital market regulations in Indonesia and Malaysia. This study highlights the role of Indonesia's Financial Services Authority (OJK), which has largely been discussed in the existing literature, but has not had a comprehensive review of the effectiveness of the Islamic Capital Market. This research builds on previous research, emphasizing the role of the OJK in market regulation, This study uses a library research approach combined with a comparative approach to analyze the comparative governance framework and regulatory practices in the two countries. The survey results show that as of April 2019, Indonesia had 629 issuers on the Indonesia Stock Exchange (IDX), of which Islamic stocks accounted for 65% of the total shares, while Malaysia had 911 issuers in 2018, and Islamic stocks accounted for 76%. This shows a significant difference in the development and acceptance of the Islamic capital market between the two countries. Furthermore, this study highlights the importance of a coordinated, independent and accountable OJK to improve the effectiveness of sharia compliance in the Indonesian capital market. Overall, both indicate that Shariah supervision and compliance in capital markets in Indonesia and Malaysia have been well implemented, but there is still room for improvement. In addition, there is a strong commitment to improving market integrity and transparency, but challenges in terms of supervision, financial literacy, and fatwa consistency need to be overcome to achieve maximum implementation.